Analisis Perlindungan Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Pencurian dengan Diversi Berdasarkan Undang-Undang No 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak - Sri Rahayu Oktavia; Hervina Puspitosari (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The Surabaya District Attorney's Office has implemented the concept of diversion settlement against children in conflict with the law as perpetrators of criminal acts with a total number of successful diversion attempts, namely in 2019 a total of 87 cases, in 2020 71 cases and in 2021 39 cases. This study uses a normative juridical method with descriptive analytical research specifications. This study aims to determine legal protection for children with diversion at the Surabaya State Prosecutor's Office as well as obstacles and efforts to overcome the implementation of diversion. The type of data used in this study is secondary data with the first formulation of the problem. How is legal protection for children as perpetrators of the crime of theft with diversion? based on Law No. 11 of 2012 concerning the Juvenile Criminal Justice System at the Surabaya District Attorney? And the second formulation of the problem are what are the obstacles to the implementation of protection for children as perpetrators of the crime of theft with diversion at the Surabaya District Attorney. The results obtained from the results of this study are the protection given to children as perpetrators of criminal acts of theft, namely with the settlement process outside the court with the concept of diversion settlement. The legal protection that is applied to the prosecutor in solving child theft cases is implemented with reference to Law 11 of 2012 concerning the Juvenile Criminal Justice System where diversion must be carried out as an effort to provide legal protection, and there are also obstacles to the implementation of diversion so that the author provides suggestions so that the implementation of diversion can be carried out even better by providing outreach to the community about the role of diversion in resolving cases of children as perpetrators of criminal acts, revision of Law no. 11 of 2012 concerning the Juvenile Criminal Justice System regarding the timeframe for implementing diversion which is lacking and the last effort is law enforcement in this case, prosecutors must instill diversion better.